EFFECT OF TRADITIONAL GAME DAM-DAMAN TO DECREASE LEVEL OF DEMENTIA ON ELDERLY - Anugrah, Wimar; Haryanto, Joni; Suarilah, Ira (Lux Mensana: Journal of Scientific Health, 2022)
Introduction.Elderly at risk of dementia caused by decrease in cognitive function, one of the treatments that is safe with no side effects is the reminiscence therapy with traditional game of dam-daman to increase cognitive function. The purpose of this study was to explain the effect of traditional game of dam-daman on level of dementia in the elderly. Method.The design of this study was Quasy Experimental design. The population was elderly in Kediri. The total sample were 20 respondents. The sampling technique was multistage random sampling method. The independent variable was a traditional game of dam-daman, the dependent variable was level of dementia. Data were collected using MMSE (Mini Mental State Examination) questionnaires and analyzed using Paired t-test and Independent T-test with a significance level of α ≤0.05. Results&Analysis.The therapeutic effect of traditional game of dam-daman  to decrease level of dementia on elderly (p = 0.000). There was any significant difference between the control group dan the treatment group after intervention traditional game of dam-daman. Discussion.Traditional game of dam-daman can improve cognitive function with dementia in the elderly. Elderly can apply the traditional game of dam-daman to help them memories. The future studies could add to the respondents and determine the factors according to the characteristic of respondent.